Fibrotic remodeling of left ventricle in the murine remnant kidney model of chronic kidney disease is independent of arterial hypertension. (25th November 2020) - Kazakov, A; Hermann, J; Jankowski, V; Speer, T; Maack, C; Laufs, U; Jankowski, J; Boehm, M; Werner, C
Abstract: Background: Cardiac fibrosis and arterial hypertension are common in patients with chronic kidney disease (CKD). We studied the mechanisms of cardiac fibrogenesis and the role of blood pressure in mice with CKD. Methods and results: 10-week-old male C57/BL6N (BL6) and SV129 wildtype (WT) mice were underwent 5/6 nephrectomy (remnant kidney model, RKM) or sham operation for 10 weeks. RKM significantly elevated plasma creatinine and urea. RKM elicited both interstitial and replacement renal and left ventricular (LV) (BL6: SHAM 5.6±0.4%, RKM 7.3±0.7%, p=0.04; SV129: SHAM 6.0±0.5%, RKM 14±2%, p=0.001) fibrosis as assessed by picrosirius red staining. In parallel, the number of cardiac fibroblasts per mm 2 (BL6: SHAM 36±4, RKM 85±13, p=0.001; SV129: SHAM 82±11, RKM 200±34, p=0.006) was increased in RKM mice. With regard to possible mechanisms, cardiac oxidative stress as shown by co-immunostaining for intracellular fibronectin and 8-hydroxyguanosine (BL6: SHAM 44±14%, RKM 60±24%, p=0.03; SV129: SHAM 51±6%, RKM 70±7%, p=0.04) and the percentage of CXCR4+ fibroblasts in the myocardium (BL6: SHAM 47±5%, RKM 62±4%, p=0.04; SV129: SHAM 63±5%, RKM 81±3%, p=0.005) were increased. Furthermore, the number of circulating CD45+ / collagen I+ fibrocytes (FACS) in the peripheral blood was increased by RKM in BL6 (SHAM 100±23%, RKM 443±252%, p=0.04) and diminished in SV129 (SHAM 100±19%, RKM 43±11%, p=0.01), while an opposite regulation was seen in the bone marrow. To further confirm the role of bone-marrow derived fibroblasts in renal and cardiac remodeling 10-week-old WT BL6 mice were subjected to transplantation of bone marrow from 10-week-old WT BL6 mice expressing green fluorescent protein (GFP)+ ubiquitously. 28 days later, RKM or SHAM-operation was performed. RKM significantly increased the number of GFP+ fibroblasts in kidney and LV-myocardium. CKD significantly decreased myocardial capillarization assessed by immunostaining for podocalyxin in both mouse lines. In parallel, myocardial protein expression of fibrosis regulators fibronectin, collagen I, CTGF and Hif1a were up-regulated and expression of the active form of eNOS (phospho-S1177) was reduced. As a possible confounder, tail-cuff blood pressure was moderately enhanced (Ø 30mmHg) 9 weeks after nephrectomy. In a control experiment using the vasodilator hydralazine (250 mg/L/day), peripheral blood pressure was equalized in all 4 experimental groups, but the extent of LV fibrosis and expression of the above-mentioned fibrosis markers remained unchanged. Conclusions: Chronic kidney disease in the RKM model elicits left ventricle fibrosis by increasing myocardial protein expression of fibrosis regulators, reduction of myocardial capillarization and mobilization / recruitment of circulating fibroblasts, independently of blood pressure. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Deutsche Forschungsgemeinschaft